Identification of spermatogenesis-associated changes in DNA methylation induced by maternal exposure to chemicals in male germ cells - Yukiko Tando; Yasuhisa Matsui (STAR Protocols, 2022)
Summary: It is now recognized that maternal environmental factors, including chemical exposure and nutritional conditions, alter DNA methylation patterns in fetal germ cells, subsequently affecting germ cell development as well as offspring phenotypes. Here, we describe steps for detecting DNA methylation changes in mouse germ cells isolated from both embryonic and spermatogenic stages after maternal exposure to a chemical compound.For complete details on the use and execution of this protocol, please refer to Tando et al. (2021).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.